Undifferentiated Febrile Illnesses Amongst British Troops in Helmand, Afghanistan. Issue 2 (1st June 2011) - Bailey, Mark S; Trinick, TR; Dunbar, JA; Hatch, R; Osborne, JC; Brooks, TJ; Green, AD
Abstract : Objectives: Undifferentiated febrile illnesses have been a threat to British expeditionary forces ever since the Crusades. The infections responsible were identified during the Colonial Era, both World Wars and smaller conflicts since, but nearly all remain a significant threat today. Undiagnosed febrile illnesses have occurred amongst British troops in Helmand, Afghanistan since 2006 and so a fever study was performed to identify them. Methods: From May to October 2008, all undifferentiated fever cases seen at the British field hospital in Helmand, Afghanistan were assessed using a standard protocol. Demographic details, clinical features and laboratory results were recorded and paired serum samples were sent for testing at the UK Special Pathogens Reference Unit (SPRU). Results: Over 6 months, there were 26 cases of "Helmand Fever" assessed and 23 diagnoses were made of which 12 (52%) were sandfly fever, 6 (26%) were acute Q fever and 5 (22%) were rickettsial infections. Four cases had co-infections and 7 cases were not diagnosed (mostly due to inadequate samples). The clinical features and laboratory results available at the British field hospital did not allow these diseases to be distinguished from each other. The exact type of rickettsial infection could not be identified at SPRU. Conclusions: These cases probably represent the "tip of an iceberg" for British and Allied forces. More resources for diagnostic facilities and follow-up of patients are required to improve the management and surveillance of "Helmand Fever" cases; until then doxycycline 100 mg twice daily for 2 weeks should be given to all troops who present with an undifferentiated febrile illness in Helmand, Afghanistan. Patients with acute Q fever should be followed-up for at least 2 years to exclude chronic Q fever. Prevention of these diseases requires a better understanding of their epidemiology, but prophylaxis with doxycycline and possibly Q fever vaccine should be considered.